Mechanism and kinetics of ultra‐high molecular weight polytetrafluoroethylene sintering. Issue 21 (2nd June 2014) - Ganguly, Ranadip; Lesser, Alan J.
ABSTRACT The effect of sintering time on the melt evolution of Ultra‐High Molecular Weight Polytetrafluoroethylene was studied in situ by high temperature Wide Angle X‐ray Scattering, and by cyclic thermal loading profiles within a Differential Scanning Calorimeter (DSC) and Thermo‐Mechanical Analyzer (TMA). Results obtained from these techniques support the concept of molecular ordering in the melt state as a function of sintering time well above the melting temperature. TMA, which is not a conventional technique for monitoring thermal transitions, is shown to be sensitive enough for such purposes. Both DSC and TMA exhibit nonequilibrium melt behavior even 30°C above its equilibrium melting temperature for long time periods. A correlation between the DSC and TMA results is established. The cyclic thermal profile leads to a dramatic growth in enthalpy of crystallization/melting. The mechanism for this growth is associated with two independent processes; isothermal annealing at the sintering temperature and lamellar thickening in the solid state. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40967.